MODERASI KOMITMEN AFEKTIF, TERHADAP HUBUNGAN MASA KERJA DAN PERCEIVED EXTERNAL PRESTIGE DENGAN KINERJA KARYAWAN - Gracia Elora Mujianto; Indarto Indarto (Universitas Semarang, 2021)
This reserach aims to optimize employee performance by analyzing the influence of work period and perceived external prestige on employee performance with affective commitment as moderating variable. The research sample was 53 employees. Research data processing by smartPLS analysis version 3.2.8. The analytical tools used are construct validity and reliability, discriminant validity test, cross loading test, R-square test, total effect test, relevant predictive test, fit model test and path coefficient test for hypothesis testing. In the R-square test, 85.9% of employee performance variables are influenced by work period and perceived external prestige. The results of research data processing show that the value of work period hypothesis testing and perceived external prestige on employee performance is significant positive then the hypothesis is accepted, affective commitment weakens the relationship between work period and employee performance, and affective commitment strengthens the moderation relationship between perceived external prestige and employee performancePenelitian ini bertujuan untuk bagaimana mengoptimalkan kinerja karyawan dengan menganalisis Pengaruh Masa Kerja dan Perceived External Prestige terhadap Kinerja Karyawan dengan Komitmen Afektif Sebagai Variabel Moderating. Sampel penelitian sebanyak 53 karyawan. Pengolahan data penelitian menggunakan analisa smartPLS versi 3.2.8. Alat analisis yang digunakan adalah uji validitas dan realibilitas konstruk, uji validitas diskriminan, uji cross loading, uji R-square, uji pengaruh total, uji predictive relevan, uji model fit dan uji koefisien jalur untuk pengujian hipotesis. Pada pengujian R-square sebesar 85,9% variabel kinerja karyawan dipengaruhi oleh masa kerja dan perceived external prestige. Hasil pengolahan data penelitian menunjukkan nilai pengujian hipotesis masa kerja dan perceived external prestige terhadap kinerja karyawan adalah positif signifikan sehingga hipotesis diterima, komitmen afektif memperlemah hubungan masa kerja terhadap kinerja karyawan, dan komitmen afektif memperkuat hubungan moderasi antara perceived external prestige terhadap kinerja karyawan.